The mental health benefits of community helping during crisis: Coordinated helping, community identification and sense of unity during the COVID‐19 pandemic. (5th April 2021) - Bowe, Mhairi; Wakefield, Juliet R. H.; Kellezi, Blerina; Stevenson, Clifford; McNamara, Niamh; Jones, Bethany A.; Sumich, Alex; Heym, Nadja
Abstract: Communities are vital sources of support during crisis, providing collective contexts for shared identity and solidarity that predict supportive, prosocial responses. The COVID‐19 pandemic has presented a global health crisis capable of exerting a heavy toll on the mental health of community members while inducing unwelcome levels of social disconnection. Simultaneously, lockdown restrictions have forced vulnerable community members to depend upon the support of fellow residents. Fortunately, voluntary helping can be beneficial to the well‐being of the helper as well as the recipient, offering beneficial collective solutions. Using insights from social identity approaches to volunteering and disaster responses, this study explored whether the opportunity to engage in helping fellow community members may be both unifying and beneficial for those engaging in coordinated community helping. Survey data collected in the UK during June 2020 showed that coordinated community helping predicted the psychological bonding of community members by building a sense of community identification and unity during the pandemic, which predicted increased well‐being and reduced depression and anxiety. Implications for the promotion and support of voluntary helping initiatives in the context of longer‐term responses to the COVID‐19 pandemic are provided. Please refer to the Supplementary Material section to find this article's Community and Social Impact Statement .